The Influence of Glaucoma as a Comorbidity on Cytokine Expression in Aqueous Humor of Patients with Fuchs Endothelial Corneal Dystrophy and Bullous Keratopathy - N. V. Fisenko; T. A. Demura; G. A. Osipyan; K. S. Avetisov (Oftalʹmologiâ)
Purpose: to evaluate the effect of primary open-angle glaucoma (POAG) as a comorbidity on cytokine expression in aqueous humor (AqH) of patients with Fuchs endothelial corneal dystrophy (FECD) and bullous keratopathy (BK).Patients and methods. In this prospective consecutive case study 58 patients (58 eyes) were divided into 2 main groups. Group 1 (22 patients with FECD) included 11 patients with coexisting POAG II–IIIA (group 1a) and 11 patients without ocular comorbidity (group 1b). Group 2 (28 patients with BK) consisted of 19 patients with coexisting POAG II–IIIA (group 2a) and 9 patients without ocular comorbidity (group 2b). Group 3 (control) included 8 patients with cataract. The patients of groups 1 and 2 underwent endothelial keratoplasty. Intraoperatively obtained recipients’ Descemet’s membranes (DMs) were investigated histologically (hematoxylin/eosin staining). A total of 58 AqH samples were collected from consecutive patients who underwent endothelial keratoplasty (groups 1a, 1b, 2a, 2b) or cataract surgery (controls). The AqH levels of cytokines (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12 (p70), IL-13, IL-17, G-CSF, GM-CSF, IFN-γ, MCP-1, MIP-1β and TNF-α) were compared among the groups.Results. Clinical diagnoses of FECD (group 1) and BK (group 2) were confirmed by the results of morphologic study. The levels of IL-8, MCP-1, IFN-γ were significantly higher in AqH samples from FECD and BK groups (regardless of the presence or absence of POAG) compared with the controls. IL-6 level was significantly elevated in FECD with coexisting POAG (group 1a) and BK (groups 2a and 2b) than in the controls. The influence of POAG on the local inflammation in FECD and BK is confirmed by the increased level of MIP-1β and the low concentration of GM-CSF compared with the controls. Among BK eyes (groups 2a and 2b), POAG as a comorbidity (group 2a) was associated with decreased level of IL-12. FECD with coexisting POAG was characterized with lower level of IL-13 in AqH than in the controls.Conclusions. POAG as a comorbid pathology in patients with FECD leads to high immune response mediated by cytokines expression. BK regardless of coexisting POAG is associated with severe local immune inflammation.